(3GdMQcGJ GdafjI efP YGe 1945(B/s ((3eQcR GdTGQbI ddEHOGY GdacQj, hRGQI GdKbGaI h GdEYdGe; s)
Title translation: Art Movements since 1945. Eduar Lucie Simth. Translation: Ashraf Rafiq Afifi.
Arabic
Keywords: N5300-7418 Visual Arts- History